Molecular Spectrum of Autosomal Dominant Hypercholesterolemia in France - Marduel, Marie (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Autosomal Dominant Hypercholesterolemia (ADH), characterized by isolated elevation of plasmatic LDL cholesterol and premature cardiovascular complications, is associated with mutations in 3 major genes: LDLR (LDL receptor), APOB (apolipoprotein B) and PCSK9 (proprotein convertase subtilisin-kexin type 9). Through the French ADH Research Network, we collected molecular data from 1358 French probands from eleven different regions in France. Mutations in the LDLR gene were identified in 1003 subjects representing 391 unique events with 46.0% missense, 14.6% frameshift, 13.6% splice, and 11.3% nonsense mutations, 9.7% major rearrangements, 3.8% small in frame deletions/insertions, and 1.0% UTR mutations. Interestingly, 175 are novel mutational events and represent 45% of the unique events we identified, highlighting a specificity of the LDLR mutation spectrum in France. Furthermore, mutations in the APOB gene were identified in 89 probands and in the PCSK9 gene in 10 probands. Comparison of available clinical and biochemical data showed a gradient of severity for ADH-causing mutations: FH=PCSK9>FDB>‘Others’ genes. The respective contribution of each known gene to ADH in this French cohort is: LDLR 73.9%, APOB 6.6%, PCSK9 0.7%. Finally, in 19.0% of the probands, no mutation was found, thus underscoring the existence of ADH mutations located in still unknown genes. © 2010 Wiley-Liss, Inc.